2018
DOI: 10.1038/s41598-018-32679-6
|View full text |Cite
|
Sign up to set email alerts
|

Lath formation mechanisms and twinning as lath martensite substructures in an ultra low-carbon iron alloy

Abstract: Lath martensite is the dominant microstructural feature in quenched low-carbon Fe-C alloys. Its formation mechanism is not clear, despite extensive research. The microstructure of an Fe-0.05 C (wt.%) alloy water-quenched at various austenitizing temperatures has been investigated using transmission electron microscopy and a novel lath formation mechanism has been proposed. Body-centered cubic {112}〈111〉-type twin can be retained inside laths in the samples quenched at temperatures from 1050 °C to 1200 °C. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 32 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…The orientation of the NW is not completely random because the diffraction spots indicated by the blue and red rectangles in Figure are assignable to ones when it is rotated ±20° and ±25° with the growth direction as an axis. The unusual orientation that is not a common habit plane in bulk is probably due to a sizable uniaxial anisotropy (NW shape) that causes different stress as compared to that of bulk. In order to make thinner single-crystal Fe NWs, a more suitable precursor such as an organometallic compound is needed to decrease the growth temperature because Fe NWs could grow only at around 800 °C as long as FeCl 2 was used as the precursor.…”
Section: Resultsmentioning
confidence: 99%
“…The orientation of the NW is not completely random because the diffraction spots indicated by the blue and red rectangles in Figure are assignable to ones when it is rotated ±20° and ±25° with the growth direction as an axis. The unusual orientation that is not a common habit plane in bulk is probably due to a sizable uniaxial anisotropy (NW shape) that causes different stress as compared to that of bulk. In order to make thinner single-crystal Fe NWs, a more suitable precursor such as an organometallic compound is needed to decrease the growth temperature because Fe NWs could grow only at around 800 °C as long as FeCl 2 was used as the precursor.…”
Section: Resultsmentioning
confidence: 99%
“…The dislocations, as the common substructure along with the uncommon {112} < 111 > type nanotwins, were observed in the martensitic laths of the heat-treated specimens. It has been reported that the twins were initially formed at the M s and then transformed into laths with internal dislocations during the subsequent auto-tempering process [26]. The M s of the TIQ-treated specimen was measured to be lower than that of the DQ-treated one, and the auto-tempering of twins was consequently restrained during the TIQ treatment.…”
Section: Quenching Effect On Microstructurementioning
confidence: 94%
“…However, in the Fe-C system, there are various reports, and the correlation between a lower transformation point and twinning has not necessarily been obtained. Recently, it is reported by Ping et al that the lath martensite seems to have the twins as the dominant microstructural feature in the low-carbon Fe-0.1%C alloys quenched at temperatures only from 1323K to 1473K [16]. Under the TEM observations, several types of twinned morphologies such as short twins normally inclined to the lath boundary, and long twins having more straight or flat boundary planes are reported.…”
Section: Introductionmentioning
confidence: 95%